IDENTIFIKASI DAN TROUBLESHOOTING MEKANISME KATUP PADA MESIN DIESEL MITSHUBISHI PS 100 - Budiyono, Budiyono; Prasetyo, Imam; Rifqi, Muhammad (Universitas Muhammadiyah Pekajangan Pekalongan, 2019)
n the automotive world, vehicles have several systems and mechanisms that influence each other to make a vehicle work optimally. One of the important mechanisms in a vehicle is the valve mechanism. Four stroke engines have intake, compression, effort and exhaust strokes. In this final report, the purpose of this report is to identify the valve mechanism, which aims to determine the maintenance and inspection of the valve mechanism of the Mitsubishi PS 100 diesel engine and to find out the symptoms of damage that often occur in the valve mechanism of the Mitsubishi PS 100 diesel engine, how it works, and how to check it. Based on the results of the Final Project Identification and Troubleshooting of the valve mechanism, that the inspection of the valve mechanism is in good condition and there are components that have been replaced, namely valve seals and valve clearance adjustments.Keywords : Valve mechanism, Diesel engine, Mitsubishi PS 100